Higher Activity of an Aldehyde Oxidase in the Auxin-Overproducing superroot1 Mutant of Arabidopsis thaliana - Seo, Mitsunori (American Society of Plant Physiologists, 1998)
Aldehyde oxidase (AO; EC 1.2.3.1) activity was measured in seedlings of wild type or an auxin-overproducing mutant, superroot1 (sur1), of Arabidopsis thaliana. Activity staining for AO after native polyacrylamide gel electrophoresis separation of seedling extracts revealed that there were three major bands with AO activity (AO1–3) in wild-type and mutant seedlings. One of them (AO1) had a higher substrate preference for indole-3-aldehyde. This AO activity was significantly higher in sur1 mutant seedlings than in the wild type. The difference in activity was most apparent 7 d after germination, the same time required for the appearance of the remarkable sur1 phenotype, which includes epinastic cotyledons, elongated hypocotyls, and enhanced root development. Higher activity was observed in the root and hypocotyl region of the mutant seedlings. We also assayed the indole-3-acetaldehyde oxidase activity in extracts by high-performance liquid chromatography detection of indole-3-acetic acid (IAA). The activity was about 5 times higher in the extract of the sur1 seedlings, indicating that AO1 also has a substrate preference for abscisic aldehyde. Treatment of the wild-type seedlings with picloram or IAA caused no significant increase in AO1 activity. This result suggested that the higher activity of AO1 in sur1 mutant seedlings was not induced by IAA accumulation and, thus, strongly supports the possible role of AO1 in IAA biosynthesis in Arabidopsis seedlings.